Pola Komunikasi Masyarakat Osing di Era Media - Serikit, Poundra Swasty Ratu Maharani (KOMUNITAS)
As  one  of  traditional  community  in  Indonesia,  Lare  Osing  of  Kemiren Village  is  capable  of  maintaining  their  local  identity  while  welcoming  the ever-improving  modern  technology  and  information.  Their  natural characteristic  is  indicated  by  their  still-existing traditional  social institutions which claim relatively high position in the community. However, the  community  somehow  manages  to  open  themselves  towards  a  more modern and sophisticated form of institution. The objective of this writing is to  describe  the  Communication  Pattern  of  Osing  Community  of  Kemiren Village  of  Glagah  Subsdistrict  of  Banyuwangi  Regency,  East  Java  in  the mass media age.